SIMULACRA AND HYPERREALITY IN BLADE RUNNER 2049 (2017) - Kurniawan, Farid (LINGUA LITERA : journal of english linguistics and literature, 2024)
Today's world is characterized by the era of simulation and hyperreality, with manyartificial realities that take over or even replace reality itself. Many aspects can now becreated or simulated through the manipulation of advanced technology, Jean Baudrillardcalls this the phenomenon of “hyperreality”. The movie Blade Runner 2049 tells the storyof this condition where artificial things are flooding the reality, and the replicants can evenreplace the role of humans themselves. In this movie, the artificially engineered human iscalled 'replicant'. Jean Baudrillard's simulacra analysis is the methodology that theresearcher uses to analyze the film, as well as taking a qualitative approach. This method isdone by observing the entire content of the movie, as well as examining various signs, bothverbal and non-verbal, to see the relationship between the Blade Runner 2049 with JeanBaudrillard's hyperreality concept. The phenomenon of artificial humans or replicants, aswell as advanced virtual technology and advanced manipulation by technology is veryrepresentative of Baudrillard's thinking. Where the world of the future, depicted as full ofdarkness due to the development of technology itself. Not only does it replace the role ofhumans, but even trying to surpass God.